Wake characteristics of large-scale wind turbines - Wang, Y.; Leble, V.; White, M.; Barakos, G.N. (My University, 2015)
The next generation of large-scale wind turbines will exceed 10 MW of rated power and will reach rotor diameters of about 200 m. Their rotor aerodynamics are also extreme with Reynolds numbers that reach 40 million. The wakes generated by these wind turbines cover a very large area downstream of their installation positions which increases the possibility that the wake vortices generated by these large wind turbines may affect passing-by flying vehicles. In this paper a CFD study of a large wind turbine was carried out to predict the power curves and aerodynamic loads on the rotor blades. Flow control devices of active leading and trailing edge flaps were also considered in the CFD study and the effects of flaps were investigated. The near wake flow was captured in the CFD study and the flaps add more complexity to the wake flow. To study the potential wind turbine wake encounters by aircraft, engineering wake models were developed to predict the wind turbine far wakes. The wake induced velocity fields were integrated into an aircraft flight dynamics model to simulate wind turbine wake encounter scenarios, designed for a light aircraft approaching an airport, where a wind turbine is installed. The severity of the wind turbine wake encounter was analysed using off-line flight simulations. The off-line simulation results indicated that the wake encounter severity was highly dependent on the ways that the wake vortex circulation and the core size were calculated, which suggested that field measurements of large wind turbines wake flow are needed to verify the modelling and CFD results.
Keywords: Operational Aspects